2016
DOI: 10.3748/wjg.v22.i21.5088
|View full text |Cite
|
Sign up to set email alerts
|

Blood neutrophil-lymphocyte ratio predicts survival after hepatectomy for hepatocellular carcinoma: A propensity score-based analysis

Abstract: Preoperative NLR ≥ 2.81 may be an indicator of poor DFS and OS in patients with HCC undergoing surgery. Preoperative NLR ≥ 2.81 may be a good complementary indicator of poor OS when elevated AFP levels provide no prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 26 publications
2
38
0
3
Order By: Relevance
“…Higher NLR level was associated with poor disease-free survival and overall survival [2527]. Our study found that NLR > 3.27 may be an indicator of poor overall survival in patients with HCC and T2DM.…”
Section: Discussionmentioning
confidence: 54%
“…Higher NLR level was associated with poor disease-free survival and overall survival [2527]. Our study found that NLR > 3.27 may be an indicator of poor overall survival in patients with HCC and T2DM.…”
Section: Discussionmentioning
confidence: 54%
“…Sensitivity analysis showed that the combined HR of OS had high stability by omitting any single study, for that the pooled HRs ranged from 1.51 (95% CI 1.37, 1.66) after omitting the study of Aino et al to 1.53 (95% CI 1.39, 1.69) after omitting the study of Yang et al . High stability was also found in subgroups of LR, LT, HAIC, and RFA.…”
Section: Resultsmentioning
confidence: 98%
“…However, the mechanism or precise correlation between inflammation response and malignancies has not been clarified. Previous studies have indicated that the pretreatment NLR was an important prognostic factor in patients with HCC after each treatment . The molecular mechanism of the prognostic role of NLR may involve many factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Hepatectomy is considered one of the most effective curative treatments for many patients with HCC, yet long-term survival remains less than satisfactory because of the high frequency of postoperative tumor recurrence. 4 Predicting which patients are more likely to experience recurrence after hepatectomy may help guide their postoperative management.…”
Section: Introductionmentioning
confidence: 99%